Transcriptomic Analysis Reveals the Positive Role of Abscisic Acid in Endodormancy Maintenance of Leaf Buds of Magnolia wufengensis - Wu, Kunjing; Duan, Xiaojing; Zhu, Zhonglong; Sang, Ziyang; Zhang, Yutong; Li, Haiying; Jia, Zhongkui; Ma, Luyi (Frontiers in Plant Science, 2021)
Magnolia wufengensis (Magnoliaceae) is a deciduous landscape species, known for its ornamental value with uniquely shaped and coloured tepals. The species has been introduced to many cities in south China, but low temperatures limit the expansion of this species in cold regions. Bud dormancy is critical for plants to survive in cold environments during the winter. In this study, we performed transcriptomic analysis of leaf buds using RNA sequencing and compared their gene expression during endodormancy, endodormancy release, and ecodormancy. A total of 187,406 unigenes were generated with an average length of 621.82 bp (N50 = 895 bp). In the transcriptomic analysis, differentially expressed genes involved in metabolism and signal transduction of hormones especially abscisic acid (ABA) were substantially annotated during dormancy transition. Our results showed that ABA at a concentration of 100 μM promoted dormancy maintenance in buds of M. wufengensis. Furthermore, the expression of genes related to ABA biosynthesis, catabolism, and signalling pathway was analysed by qPCR. We found that the expression of MwCYP707A-1-2 was consistent with ABA content and the dormancy transition phase, indicating that MwCYP707A-1-2 played a role in endodormancy release. In addition, the upregulation of MwCBF1 during dormancy release highlighted the enhancement of cold resistance. This study provides new insights into the cold tolerance of M. wufengensis in the winter from bud dormancy based on RNA-sequencing and offers fundamental data for further research on breeding improvement of M. wufengensis.